5PSQ-012 Are 12 months of treatment with monoclonal antibodies sufficient for migraine attack prevention?. (23rd March 2022) - Fresan, D; Lacalle, E; Calvo, M; Tejada, D; Albalat Torres, A; Ortega, I; Pino, A; Erdozain, S; Larrayoz, B; Sarobe, M
Abstract : Background and importance: Monoclonal antibodies (MAB) galcanezumab, erenumab and fremanezumab have been recently incorporated into the treatments for migraine attack prevention. All have proven to be safe and effective at reducing the number of migraine days (MD) versus placebo in short-duration clinical trials. However, some uncertainties remain unsolved, such as the optimal therapy duration. Clinical practice guidelines recommend treatment maintainance for 12 months. Aim and objectives: To analyse patients' clinical situation after the year of treatment. Material and methods: Prospective and observational study conducted in a tertiary hospital between December 2019 and August 2021. After 12 months, neurologists decide whether the patient should continue with chronic treatment or, as recommended, stop and ask for re-evaluation if migraine worsens. All patients are reviewed 3 months after discontinuation. Pharmacists' tasks range from validating and dispensing all treatments to medication counselling and follow-up. Results: 97 patients completed the first 12-month treatment course. 15.5% (15) were maintained chronically (8 as they had a strong likelihood of worsening if discontinued; 3 because MD diminished although they still had >15 days monthly; 2 since an effect was demonstrated during the last 3 months of treatment and 2 due to previous failure of dose reduction attempts). 32% (31) of patients required treatment reintroduction: 8 in less than 3 months (mean 1.57 (0–2) months) and 24 in ≥3 months (mean 4.08 (3–6) months). 21 of them have reached the second course 3 months' evaluation and all continue with effectiveness. 6.2% (6) changed to another preventative therapy ( botulinum toxin, mainly) when their condition worsened and 2.1% (2) to another MAB. 8.2% (8) switched directly to another MAB due to poor response to the first one. 36% (35) remain in a clinically stable condition without a preventive therapy (20 after ≥3 months and 15 in the first 3 months). Conclusion and relevance: Effect of treatment remains for at least 3 months after discontinuation in 45% (44) of patients. 24% (23) of patients are either maintained chronically or need an early re-start. 64% (62) of patients still need preventive therapy for migraine attacks after 12 months of therapy. Further studies with larger samples are required to establish the optimal duration for MAB as patients tend to worsen with time. Will they end up being chronic medications? References and/or acknowledgements: Conflict of interest: No conflict of interest